Investigating The Relationship Between Trade Liberalization And Foreign Direct Investment: Evidence From Algeria - Daoudi Mohamed; Kadri Mohamed (My University, 2019)
This paper explores the causal relationship among trade liberalization, foreign direct investment, financial liberalization and economic growth for Algeria over the period 1995–2017. The Autoregressive Distributed Lag (ARDL) bounds test is used to test for the presence of co-integration, whereas the Toda and Yamamoto test is used for direction of causality. The findings of ARDL bounds test validate the existence of co-integration among the included variables. Further, the Toda and Yamamoto test affirms that there is bidirectional causality between trade liberalization and foreign direct investment. Additionally, there is a unidirectional causality running from financial liberalization to foreign direct investment as well as unidirectional causality running from economic growth to foreign direct investment.
Keywords: Foreign direct investment ; Trade liberalization ; Toda-Yamamoto test ; Algeria